Strength Properties of Cellular Lightweight Concrete Bricks Using Sorong Sand - Titarsole, Daniel Khen; Bali, Ika; Sudjatmiko, Eddy Triyanto (President University, 2025)
Infrastructure growth in Sorong requires innovative construction materials that are efficient, durable, and environmentally friendly. Cellular Lightweight Concrete (CLC) bricks are proposed as an alternative to conventional red bricks. This study investigates the compressive strength and density of CLC bricks made with Sorong sand, using Cikarang sand as a comparison. Laboratory trials were conducted to develop a mix design with a target density of 800 kg/m³. The results show that CLC bricks using Sorong sand reached densities of 821.73–867.16 kg/m³ and compressive strengths of 0.81–1.11 MPa at curing ages of 3, 7, and 14 days. These values were slightly lower than those of Cikarang-sand bricks, which achieved densities of 831.11–879.01 kg/m³ and strengths of 0.81–1.26 MPa. The reduced strength of Sorong-sand bricks is related to their lower density. Nonetheless, testing confirmed that Sorong sand meets fine aggregate specifications, making it suitable for CLC brick production and supporting local infrastructure development.